Using accurate detection tools to develop a successful management strategy for lentil and chickpea viruses in farmers' fields in the highlands of Ethiopia - Kumari, Safaa; Moukahel, Abdulrahman; Ademe, Anteneh; Aynewa, Yetsedaw; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2022)
Since 2019, farmers in the highlands of Ethiopia are losing their chickpea and lentil crops because of virus epidemics, and lentil production area in Ethiopia was reduced due to the virus infection. Based on FAOSTAT, lentil production (tonnes) and Area Harvested (ha) in Ethiopia decreased from 166,274 tonnes and 113,685 ha during 2016 to 113,018 tonnes and 84,512 ha during 2020, respectively (FAOSTAT, 2022). Knowing the exact identity of viruses affecting both crops is essential for breeding for resistance and crop management purposes. To achieve this, field surveys were carried out for four consecutive seasons (2019-2022) in collaboration between ICARDA and Ethiopian researchers, using up-to-date detection tools to monitor virus incidence and distribution on lentil and chickpea crops in the highlands of Ethiopia. Data generated can be used by plant pathologists, scientists, breeders, plant protection organizations, policy makers, National agricultural research, and extension agencies to mitigate the viral diseases.